Maize farmers' responses to Spodoptera frugiperda in Indonesia and management practices: a case study in West Java. Issue 1 (1st December 2022) - Asfiya, W; Subagyo, V N O; Maharani, Y; Fatimah,; Ruswandi, A; Winara, A; Diana, M; Nur, Y H; Indrajaya, Y
Abstract: The fall armyworm Spodoptera frugiperda (FAW) is an alien invasive species that attacked maize crops in Indonesia in 2019. This pest is reported to cause significant damage, so control measures are required. Understanding farmers' perceptions, knowledge, and management of FAW are important steps towards developing sustainable integrated management strategies as farmers are important actors in this context. A total of 102 farmers were selected for interviews from Bandung, Garut, and Sumedang districts. We found that most respondents surveyed were of productive ages, and the majority were male. Most farmers in all districts were able to differentiate FAW based on distinguishing morphological features and level of damage on infested maize plants. Farmers consider a significant yield reduction if the pest is not controlled. However, due to limited information, most farmers relied on chemical insecticides to control this pest. Farmers in Sumedang, nevertheless, also practiced mechanical and cultural methods for FAW management. In addition, extension agents and farmer groups can help improve farmers' knowledge of the fall armyworm related to control measures applied to manage FAW. Therefore, enhancing farmers' capacity through participation in training courses and farmer groups, as well as extension agents' role as information sources about FAW should be increased.